Wear mechanisms of thin dental composites - Osiewicz, Magdalena A.; Werner, Arie; Roeters, Franciscus J. M.; Kleverlaan, Cornelis J. (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveIn patients with severe wear, the performance of restorative materials is challenging, especially in load-bearing thin restorations. In this study, we aimed to investigate the wear rate in thin-layered restoration (1.5 mm) compared to more bulky restorations (3 mm), where less deformation and stress within the material are expected.MethodsThe wear rates of four resin-based composites were measured using one layer of 3-mm thickness compared to a thin-layered specimen of 1.5-mm composite, which was supported by a flexible layer of 1.5-mm silicone impression material. Two- and three-body wear were measured using the ACTA wear device. Scanning electron microscopy analysis was performed to detect the surface alterations. One- and two-way ANOVA and Tukey’s post hoc test were used to analyze differences in wear values.ResultsThe two-body wear of the 1.5-mm specimens was significantly higher (p < 0.001) than that of the 3-mm specimens. The increase in the wear rate between the 1.5-mm and 3-mm specimens can be attributed to fatigue wear. The three-body wear of the 1.5-mm Heliomolar (HMR) specimens was significantly higher than that of the 3-mm HMR specimens. However, for the three-body wear, there was no significant difference between the 1.5-mm and 3-mm specimens of Clearfil AP-X and Clearfil Majesty ES-2.SignificanceThe results of this study show for the first time that fatigue wear plays a role in the wear mechanism of thin (1.5 mm) dental resin-based composites. Therefore, the deformation of restorations under loading should be minimized by avoiding thin restorations and flexible conditions and using resin-based composites with high E-moduli.